Improving Vocabulary Learning Through Songs for Elementary School Students Using a Constructivist Approach - Rizka, Deandra; Silvi Nur Qomariyah; Ririn Novianti; Juloanto; Wiryanto (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
The application of constructivist learning theory I considered important nowadays. When songs are introduced in the classroom the students can be more engaged. This study explores the use of constructivist learning theory in teaching English language to grade five elementary students, focusing on the effectiveness of songs as a learning tool. It investigates how songs can enhance student engagement, vocabulary retention, and concept understanding by promoting active participation. Using a descriptive quantitative approach with a case study design, data were gathered through direct observations of student engagement and document analysis of learning outcomes. The findings show that incorporating songs significantly improves student participation, making vocabulary retention easier and aiding concept comprehension by providing meaningful context. The study concludes that integrating songs into the learning process creates a more engaging and effective learning environment, helping students deepen their knowledge through active experience and social interaction. Thus, the use of songs as a learning tool can be an effective strategy in improving the quality of English language learning in elementary schools.